Students Between Rumors and Misunderstandings - Ҫoni (Kacollja Darina (European Journal of Multidisciplinary Studies, 2016)
The detailed study of the students’ conflicts among each-other intends to observe the causes and favorable conditions as a necessity in order to understand the roots of the social phenomena. This implies a comprehensive analysis of social, economical, intercultural factors which influence on its application. The study is conducted at “Aleksander Xhuvani” University in Elbasan, in the Faculty of Social Sciences, Faculty of Economics and in the Nursing Faculty. There are surveyed 400 students of these faculties. A special attention was paid even to the interviews and opinions of students, which are reflected in the interior of the study. According to the survey, there is a result; 42 percent of the students have stated that they are in conflicts with other students. This shows that we have a relation where roughly half of students are in conflict with each-other and this happens due to several factors. In this study, we are focused on rumors and misunderstandings between them as the main cause of the students’ conflicts with each-other.